Dehydroandrographolide targets CD300f and negatively regulated MRGPRX2‐induced pseudo‐allergic reaction. (21st March 2022) - Che, Delu; Zheng, Yi; Hou, Yajing; Li, Ting; Du, Xueshan; Geng, Songmei
Abstract: Mas‐related G protein‐coupled receptor X2 (MRGPRX2) mediates mast cells (MCs) activation, which is a key target for the treatment of allergic diseases. However, there are few drugs targeting MRGPRX2. Leukocyte mono‐immunoglobulin‐like receptor 3 (CD300f) is a negative regulator of FcεRΙ‐mediated MC activation. However, the regulatory effect of CD300f on MRGPRX2 remains unclear. Dehydroandrographolide (DA) is a main contributor of Andrographis paniculata (Burm.f.) Nees (family: Acanthaceae) have been shown to inhibit type I hypersensitivity. The aim of this study was to determine whether DA negatively regulated MRGPRX2‐mediated MC activation via CD300f and showed therapeutic effect on pseudo‐allergic reactions. Mouse allergic models and MC degranulation were detected in vivo and in vitro, and inflammatory mediators were detected. siRNA interference and Biacore were used to verify the target. DA inhibited pseudo‐allergic reactions by reducing vasodilation and serum cytokine levels in mice and inhibited MRGPRX2‐mediated MC activation. The regulatory effect of DA was significantly decreased after the knockdown of CD300f expression. Moreover, DA upregulated the phosphorylation level of Src homology region 2 domain‐containing phosphatase (SHP)‐1 and SHP‐2, which are key kinases in the negative regulatory signaling pathways associated with CD300f. In conclusion, DA negatively regulates MRGPRX2‐mediated MC activation via CD300f to inhibit pseudo‐allergic reactions.